Ruptured Rudimentary Horn Pregnancy: Two Case Reports (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Unicornuate uterus with rudimentary horn occurs due to failure of complete development of one Mullerian duct and incomplete fusion of the contralateral side. Pregnancy in rudimentary horn is rare and carries grave consequences to both mother and fetus. Here two case reports have been presented, both the cases were diagnosed after laparotomy. Diagnosis before rupture is challenging. So high index clinical suspicion and role of ultrasonography, resuscitation and laparotomy is necessary to prevent catastrophe.Bangladesh J Obstet Gynaecol, 2014; Vol. 29(2) : 116-119